Analisis Tingkat Literasi Ekonomi Siswa SMP Dalam Konteks Pembelajaran IPS - Triyaningsih, Lulus (Gayaku Publisher, 2025)
This study aims to analyze the level of economic literacy among junior high school students in the context of Social Studies (IPS) learning. Economic literacy is understood as the ability to comprehend basic economic concepts, apply them in real-life situations, and make rational economic decisions. The research employed a descriptive quantitative approach, involving 80 eighth-grade students of SMP Negeri 2 Purwoharjo. The research instrument consisted of an economic literacy test (30 multiple-choice items) and an attitude questionnaire (10 Likert-scale items). Content validity was examined through expert judgment, and reliability testing using Cronbach’s Alpha yielded 0.81, indicating acceptable reliability. The findings revealed that students’ overall economic literacy was at a moderate level, with an average score of 68.4. By aspect, conceptual understanding was categorized as good (74), application of concepts was low (62), and economic attitudes were moderate (69). These results highlight a gap between theoretical mastery and practical application. Therefore, IPS learning should be developed through contextual approaches, market simulations, and project-based learning to enhance students’ economic literacy.